The Marginal Notes in the Abba Gärima Gospels - Haile, Getatchew (Aethiopica, 2017)
It is clear that, due to the age of the manuscripts of the Abba Gärima Gospels and the condition in which they are preserved, some leaves of one Gospel manuscript have been inadvertently rebound with another Gospel manuscript. My presentation follows Garima I and Garima II, as titled, which have been graciously sent to me for this conference. For my personal study of the notes, I was fortunate to have access to copies made three times, first by D.M. Davies, then by Jacques Mercier, and now by HMML, the Museum and Library to which I am affiliated. Unfortunately, there are letters and words that might be lost forever unless there is a technology that can retrieve them. Also, a few people and many places will remain unidentified, at least for now, as it is not clear if two words which come following one another are names of one place or of two. As one will see, the method I followed is this: (1) editing the texts, (2) translating them into English, and (3) offering my views under ‘Commentary’. The Index helps when questioning if words that look alike are names of the same place or of different places. Conti Rossini’s edition of Liber Axumae (1909) and the study of its ‘Land Charters’ by Huntingford (1965) have been helpful. These notes are what one might call Land Charters; none of them is a colophon.